PENGARUH KUALITAS LAYANAN, CITRA PERUSAHAAN, DAN PERSEPSI HARGA TERHADAP KEPUASAN KONSUMEN (Studi Kasus Pada Pengguna Jasa Servis Kendaraan Roda Dua Di Yamaha Agung Motor Semarang) (Students' Journal of Economic and Management, 2015)
This study analyzed the quality of service (X1), the image of the company (X2), and the perception of the price (X3) on consumer satisfaction (Y). The population in this study is the great customer service yamaha motor using quality of service, corporate image, and price. The samples made with the technique of "accidental sampling" and the number of samples taken as many as 100 people. The analysis model is a linear regression. The results of the research are: (1) The results of the statistical calculation with multiple linear analysis can be seen that the quality of service does not exist a positive and significant effect, while the image of the company, and the perception that prices have a positive and significant influence on customer satisfaction. (2) The calculation of the coefficient of determination shows that the quality of service, corporate image, and perception can explain the variable price of consumer satisfaction. (3) The hypothesis that has been done in this study are: A) There is no positive and significant effect of service quality on customer satisfaction. B) There is a positive and significant influence of corporate image on customer satisfaction. C) There is a positive and significant influence perceptions of price on customer satisfaction. Keywords: Quality of service, corporate image,Perceptions of price on customer satisfaction